Implementasi Kebijakan Perlindungan Anak Korban Kekerasan di Kabupaten Kediri - Azmi Kumalasari, Whendyra; Rining Nawangsari, Ertien (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the implementation of child protection policies for victims of violence in Kediri Regency, focusing on four key variables according to George C. Edwards III's theory: communication, resources, disposition, and bureaucratic structure, using a qualitative approach. Data were gathered from interviews, observations, documentation, and relevant secondary sources such as books and scholarly articles. The research was conducted at the Office of Population Control, Family Planning, Women's Empowerment, and Child Protection (DP2KBP3A) in Kediri Regency. The findings indicate that 1) Communication success in policy implementation has been effective, marked by clear and consistent information transmission between the head of DP2KBP3A Kediri, PPA department staff, and the community. 2) Challenges persist in the resources variable concerning staff numbers and facilities like the absence of a shelter, which does not align with Edwards III's theory of implementation success. However, existing resources have been optimally utilized through information and authority. 3) Disposition has been effectively implemented, evidenced by policy implementers' high commitment to policy execution. 4) Bureaucratic structure at DP2KBP3A Kediri has been well-implemented, supporting the smooth implementation of child protection policies for victims of violence.